PEER TO PEER LENDING ON FINANCIAL TECHNOLOGY UNDER PERSPECTIVE POSITIVE LAW AND ISLAMIC LAW - Nurul Ula Ulya (Journal of Islamic Business Law, 2018)
Peer to Peer lending is a platform on financial technology that brings together creditors and debtors with online system. Financial technology is an innovation financial services that use the technology. The aims of this research is to find positive law perspective and Islamic legal perspective considering the existence of peer to peer lending products and the high risks that arised from lending with this platform. This research uses normative juridical method, with conceptual approach and statute approach. The analysis used is descriptive and summarized in inductive way that explained the result from special to general. The result obtained from this research are the regulation of peer to peer lending still not comprehensive because ithas needed some regulations in Civil Code, OJK Regulation number 77/2016, ITE law and Customer Protection law. While OJK regulation as a main regulation still contains many shortcomings and did’nt cover a legal certainty and justice yet. In Islamic law perspective peer to peer lending is allowed but must be obliged sharia terms